Mineral Supplements’ Prescribing Practices in Critically Ill Cancer Patients: A Study Investigating Physicians’ Prescribing Practices and Roles of Nutrition Support Pharmacists at a Tertiary Cancer Center - Abdelhadi, Dr. Nadine; Dabbous, Alaa; Darwish, Mariam; Jaddoua, Dr. Saad (Jordan Medical Journal, 2025)
Objective: This study aimed to explore physicians’ prescribing practices and roles of nutrition support pharmacists in managing mineral deficiencies in critically ill cancer patients admitted to intensive care units (ICU) at a tertiary cancer center. Methods: A retrospective analysis of 9949 electronic records of critically ill cancer patients admitted to the ICU from January 2020 to December 2022 was performed. All mineral supplement prescriptions by physicians and nutrition support pharmacists’ interventions were recorded. Analysis was performed utilizing the Jamovi statistical package 2022 Results: The study population comprised pediatric patients and adult patients. Major minerals were most frequently prescribed in ICU cancer patients, followed by trace minerals. Potassium was the most prescribed mineral supplement, followed by Sodium, Calcium, and Magnesium. The least prescribed was Lithium. The most frequent intervention of pharmacists was initiating mineral supplement use, followed by discontinuing mineral supplement use. The acceptance rate of interventions by physicians was 88%. Conclusion: Potassium was the most prescribed mineral supplement in critically ill cancer patients at a tertiary cancer center. Nutrition support pharmacists’ interventions were highly accepted by physicians. The prevailing intervention was the initiation of mineral supplement use. Further studies are needed to explore the barriers to implementing nutrition support services in different healthcare settings.